The making of the Avicennan tradition : the transmission, contents, and structure of Ibn Sīnā's al-Mubāḥa_tāt (The discussions) - Reisman, David C. (Islamic philosophy, theology, and science, 2002)
This volume represents a philological approach to the study of the medieval philosophy Avicenna by investigating the manuscripts and textual transmission of his philosophical correspondence with students and colleagues.